Right of the Child to Land Acquisition in Nigeria: The Capacity Challenge - Oti-Onyema, Linda Amarachi (ABUAD Private and Business Law Journal, 2018)
Realizing the indispensable place of the child in the sustainability of the human race, efforts are being intensified by the international and local communities in protectingthe rights of the child. It has been observed that much of these efforts have been centered on the person of the child rather than his property, particularly as a result of the traditional view classifying the child as a property of his parents. This paper examines the right of the Nigerian child to acquire and own land as contained in the principal statutes on land acquisition with a view to determiningthe availability of the right and the extent to which the child can enforce it. The paper found that, like adults, the child possesses a fundamental right to acquisition and ownership of property to be exercised and enforced through his guardian or trustee until he attains age of majority. However, full realization of this right is far-fetched owing to some shortcomings in our laws which include the differences in age limit of the child in the various statutes providing the child’s right to property and the variation in rules of contract applicable to the grant of the different rights of occupancy over land as contained in the Land Use Act. The paper inter alia, recommends a harmonization of both the minimum age of a child and the applicable rules.